Oxidative Stress in Non-alcoholic Fatty Liver Disease. An Updated Mini Review - Delli Bovi, Anna Pia; Marciano, Francesca; Mandato, Claudia; Siano, Maria Anna; Savoia, Marcella; Vajro, Pietro (Frontiers in Medicine, 2021)
Non-Alcoholic Fatty Liver Disease (NAFLD) is a highly complex disease caused by multiple factors, which may partly explain why it remains still orphan of an adequate therapeutic strategy. Herein we focus on the interplay between oxidative stress (OS) and the other causal pathogenetic factors. Different reactive oxygen species (ROS) generators contribute to NAFLD inflammatory and fibrotic progression, which is quite strictly linked to the lipotoxic liver injury from fatty acids and/or a wide variety of their biologically active metabolites in the context of either a two- or a (more recent) multiple parallel hits theory. An antioxidant defense system is usually able to protect hepatic cells from damaging effects caused by ROS, including those produced into the GI tract as by-products of normal cellular metabolic activities, normal or dysbiotic microbiota and/or diet through an enhanced gut-liver axis. Oxidative stress originating from the imbalance between ROS generation and antioxidant defenses is under the influence of individual genetic and epigenetic factors as well. Healthy diet and physical activity have been shown to be effective on NAFLD also with antioxidant mechanisms, but compliance is very low. Among several considered antioxidants, vitamin E has been particularly studied, however data are still contradictory. Some studies with natural polyphenols proposed for NAFLD prevention and treatment are encouraging. Probiotics, prebiotics, diet or fecal microbiota transplantation represent new therapeutic approaches, targeting the dysbiotic gut microbiota. In the near future, precision medicine taking in consideration genetic or environmental epigenetic risk factors will likely assist in selecting the treatment that could work best for a specific patient.